Modelando e simulando o comportamento de Blitzes policiais racionais - Almeida, Hellano Vieira de (2017)
Despite the great amount of scientific articles on crime that has been published in recent years, both in national and international journals, there is still insufficient investigation and little is known about the functioning characteristics of police blitzes and their decisory process. Therefore my work intends to use Search Theory in order to create a search model for the optimal decision process to stop a police blitz and to simulate and compare our results with real data. Our proposed model was constructed in such a way to guarantee the existence of the “reservation” property. The simulations induced from the model show satisfactory results in comparison with real data.